Impelementasi Pemeliharaan Jiwa (Hifz Al-Nafs) Pada Pengasuhan Anak Berbasis Keluarga - Aay Siti Raohatul Hayat (Institut Agama Islam Negeri (IAIN) Curup, 2020)
The formula for nurturing the soul always receives interesting discussions, likewise the SOS Children's Village as the largest non-governmental organization dedicated to caring for children who are abandoned and have lost their parents. The SOS Children's Village of Semarang believes that every child deserves to have a loving home by giving children supports they need to grow strong in sustaining life. This article focused on the discussion on how SOS Children's Village formulates ḥifẓ al-nafs by means of parenting styles applied in SOS. The phenomenological approach was used to see how the formulation of soul care was applied by SOS, so that the maintenance of the soul as a part of maqāṣid al-sharī'ah could be more unique due to the emphasis on applicative and empirical nourishment of the soul. SOS had three (3) work programs, namely family-based care, family strengthening programs, and disaster emergency response. The three programs were oriented towards fulfilling children's rights as an effort to nurture children's souls so that they could grow and develop like children with nuclear families, where children who lost their care would live in an SOS village with a substitute family. This concept of care involved a foster mother in each house as the center of care, other children as siblings in the family home, and the SOS Family Village. The forms of care provided by the foster mother included paying attention, supervising, interacting and giving support to the SOS children. Also, the values conveyed in this parenting included religion, love and affection, responsibility and discipline